The Impact Assessment of Front Line Demonstrations on Sesame: A Case Study in Tirap District of Arunachal Pradesh, India - Abhimanyu Chaturvedi; A. N. Tripathi; N. K. Mishra; V. K. Pandey (Archives of Current Research International, 2024)
Sesame (Sesamum indicum L.) is an important oilseed crops. The sesam’s productivity in the Tirap district is low and attempts were made to increase the area and improve the productivity by adopting high yielding variety along with integrated crop management (ICM) practices. The ICM practices including sowing of improved variety (Kaliabar), seed treatment with mancozeb @ 3 g/kg seed + neem oil application at 25-30 days after sowing + spraying of carbendazim for control of leaf spot (caused by Cersospora sesame) was demonstrated in farmer’s field. Similarly farmers were also sown at same time but they could not follow the scientific method of its cultivation. The results revealed that increase in seed yield over farmers’ practice was 30.96 and 31.26 per cent during 2017-18 and 2018-19, respectively. In terms of economics, it was observed that demo practices recorded higher net returns/ha compared to farmer’s practice during the both years. The benefit cost ratio of demo plots; during both years was 2.20 and 2.36, respectively. The technology index varied between from 42.25 per cent to 36.50 per cent; which depicting that farmers has to educate for adoption of economically viable technologies of oilseed crops in Tirap district.